"We power democracy": Exploring the promises of the political data analytics industry. Issue 3 (27th May 2019) - Simon, Felix M.
Abstract: Data-driven campaigning has been in the spotlight over several years. Yet, we still have a limited understanding of political data analytics companies: how they envision data analytics and voter targeting, their role in electoral processes and what promises they make to their clients. This article focuses on the way in which such issues are conceived of in the marketing rhetoric of the political data analytics industry. Drawing on a sample of 19 political data analytics companies it systematically explores the ways in which data analytics is envisioned and marketed as a powerful tool in electoral processes, exposing a fundamental disconnect between scholarly discourse on the one hand – often critical of the claims of these companies about the efficacy of their methods – and a highly functionary data imaginary on the other hand, actively fostered by the political data-analytics industry and the media.